The Role of Platelets in Bone Remodeling - Salari Sharif, Pooneh; Abdollahi, Mohammad (Inflammation & Allergy-Drug Targets (Discontinued), 2010)
Platelets play a critical role in wound healing and hemostasis, as well as in repairing bone fracture. The impact of platelets on inflammation and inflammatory diseases has been appreciated. It has been demonstrated that inflammation and oxidative stress are intimately involved in the pathogenesis of osteoporosis. Degranulation of platelets, anuclear cell fragments, leads to the release of different growth factors and chemoattractants affecting bone metabolism. The net effect is, however, not fully understood. The current review is aimed to examine available studies on the impact of platelets on bone health. We searched data from Scopus, PubMed and Web of Science using keywords such as platelets, osteoblasts, osteoclasts, bone, antiplatelet drugs, bone formation, and bone resorption. As hypothesis of the review is emerging, a small number of in vivo and in vitro studies were found. Based on the available data, platelets and platelet-derived numerous immune and inflammatory agents can be viewed as targets for therapeutic and/or preventive measures in osteoporosis.
Keywords: nuclear factor κB ligand (RANKL